Patient‐Derived Bladder Cancer Organoids as a Valuable Tool for Understanding Tumor Biology and Developing Personalized Treatment - Hongda Zhao; Na Lin; Vincy Wing Sze Ho; Kang Liu; Xuan Chen; Hongwei Wu; Peter Ka‐Fung Chiu; Linda Huang; Zahra Dantes; Ka‐Leung Wong; Ho‐Fai Chau; Ivan Ching‐Ho Ko; et al. (Advanced Science)
Abstract Bladder cancer (BC) is a heterogeneous disease with high recurrence rates and variable treatment responses. To address these clinical challenges, the world's first bladder cancer patient‐derived organoids (PDOs) biobank is established based on an Asian population. Thirty‐six BC‐PDOs are generated from 56 patients and demonstrated that the BC‐PDOs can replicate the histological and genomic features of parental tumors. Drug screening tests are conducted with a broad spectrum of conventional chemotherapeutic and targeted therapy drugs and identified differential drug sensitivities among the BC‐PDOs. These in vitro results are consistently supported by the PDO xenograft animal studies and patients’ clinical treatment outcomes, thereby verifying the predictive power of PDOs for drug responses in BC patients. By analyzing the genetic profiles of the PDOs, specific driver genes that correlate with drug sensitivity to two stand‐of‐care chemotherapeutics, cisplatin, and gemcitabine, are identified. Additionally, the practicality of PDOs in investigating the tumor microenvironment has been demonstrated. This study underscores the utility of PDOs in advancing the understanding of bladder cancer and the development of personalized therapeutic strategies. The BC‐PDOs biobank provides an ideal preclinical platform for supporting the development of personalized treatment strategies for BC patients. This study also provides insights into the potential mechanisms of drug resistance, paves the way for subsequent region‐specific research, and demonstrates the possibility of using PDO‐related models to direct future research in developing drugs targeting tumor microenvironments.